Theoretical Analysis of Performance of a Micro Gas Turbine Co/Trigeneration System for Residential Buildings in a Tropical Region - F., Basrawi; Yamada, Takanobu; Obara, Shin’ya (Elsevier Ltd, 2013)
This study shows performance of micro gas turbine (MGT) based cogeneration system (CGS) and trigeneration system (TGS) in residential buildings located in the area with a tropical climate. Energy, economic and environmental performance of MGT-CGS and MGT-TGS were studied. MGT-CGS consists of an MGT and an exhaust heat exchanger (EHE), whereas MGT-TGS consists of an MGT, an EHE, an absorption heat pump and a heat storage. Heat storage was essential for storing heat generated during daytime to be utilized during night-time in which heat demand was higher. MGT-TGS was a better configuration compared to MGT-CGS because it can utilize more exhaust heat and had Energy Recovery Utilized Efficiency (ηER,utilized) of 0.37 and 0.80 during daytime and night-time, respectively. Furthermore, the payback period for the MGT-TGS was also shorter than MGT-CGS, 13.8 years under highly subsidized electricity tariff. The MGT-TGS also had a higher Fuel Energy Saving Index FESI when compared to a gas turbine, but had a lower FESI when compared to a combined cycle gas turbine. MGT-CGS and MGT-TGS can also reduce pollutants especially NOx emissions compared to conventional systems.